Troubling Sociocultural Narrative Pedagogy: Implications for Art Educators. (1st October 2016) - Travis, Sarah; Hood, Emily Jean
Abstract : This article draws on a study with preservice art educators to offer theoretical perspectives on sociocultural narrative pedagogy. Informed by the work of Chicana feminist scholar Gloria Anzaldúa, the authors identify three major phenomena that manifest within sociocultural narrative pedagogy: (1) disruptions, ruptures, and breakdowns, (2) silences, refusals, and resistances, and (3) paradoxes. The authors conclude that while narrative can be a powerful pedagogical tool for addressing sociocultural difference, it is also a troubling, often paradoxical, avenue for developing critical consciousness in preservice art educators.